ANALISIS PERUBAHAN GARIS PANTAI DAN STRATEGI PENGELOLAANNYA DI PANTAI BARAT SULAWESI SELATAN - Agustina Goni; Abdul Rauf; Asbar Asbar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2018)
This study aims to: (1) analyze changes in coastlines that experience accretion and coastal abrasion; (2) analyze oceanographic factors that influence changes in coastline; (3) formulate direction of management strategies in the research areas that experience accretion and abrasion. In addition, it is expected to be able to provide information to stakeholders as a material consideration in taking the policy of managing the coastal areas of Pangkep and Pinrang Regencies. The method used in this study is analysis of shoreline changes based on survey and mapping methods, interpretation of SPOT 6 images for shoreline changes and SWOT analysis for strategy direction determination. The results of image interpretation show that the extent of shoreline changes that occurred in Pangkep Regency amounted to 38.74 Ha in the form of accretion and 13.99 Ha in the form of abrasion, whereas for Pinrang Regency the extent of shoreline change was 158.15 Ha which experienced accretion and 41.88 Ha in the form of abrasion. The results of the Coastal Coastal Management Strategy analysis based on the results of the analysis carried out there are 4 things that become tactical decisions for recommendations in coastal management efforts, namely; make special areas for coastal security and coastal conservation naturally; law enforcement and institutional strengthening; provide special allocation of space for safeguards and coastal protection; improving the quality of human resources around the coast.